2006
DOI: 10.46743/1540-580x/2006.1104
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Patient Concerns into Discharge Plans: Evaluation of a Patient-Generated Checklist

Abstract: Background: This paper reports on the effectiveness of a checklist that assists patients to transition safely and sustainably from hospital to home. Methods: Medical wards in three tertiary public hospitals in metropolitan Adelaide provided subjects during 2004. Eligible patients were English-literate and aged at least 60 years, provided written informed consent and had an unplanned hospital admission for a new medical condition. Data was excluded post-hoc if subjects had another hospital readmission for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Hospital discharge preparation tools were operationalized as planning manuals and checklists that encourage people to consider all aspects of hospital discharge, necessary arrangements, and their personal discharge readiness. The two studies evaluating such tools as a single intervention showed peoples’ appreciation for the tools with a view to their relevance and utility, but indicated no effects on the quality of discharge [ 22 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospital discharge preparation tools were operationalized as planning manuals and checklists that encourage people to consider all aspects of hospital discharge, necessary arrangements, and their personal discharge readiness. The two studies evaluating such tools as a single intervention showed peoples’ appreciation for the tools with a view to their relevance and utility, but indicated no effects on the quality of discharge [ 22 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…• No difference in ED-readmissions between the intervention group and control at 30 and 180 days (11.0% vs 14.2%; OR = 0.76; 95% CI 0.44–1.30; and 37.1% vs 36.0%; OR = 1.16; 95% CI 0.78–1.72 respectively). Grimmer, 2006, Australia [ 22 ] Hospital discharge preparation tool Before-after study Older people facing hospital discharge Intv n = 107 (mean = 70) Contr n = 210 (mean = 69) Primary: Quality of preparation for discharged (self-assessed). Secondary: Experiences with managing at home, if hospital could have done more, and use of the tool.…”
Section: Methodsmentioning
confidence: 99%
“…Hardiman and colleagues developed a patient checklist for postsurgical care for patients who had undergone ileostomy surgery [6]. Other patient checklists have been developed to aid discharge from hospital following medical admissions and one preoperative visit checklist aiming to increase parents' understanding of the surgical consent process for paediatric orthopaedic patients [7,8]. These studies suggest that patient checklists and similar interventions are feasible to use [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Other patient checklists have been developed to aid discharge from hospital following medical admissions and one preoperative visit checklist aiming to increase parents' understanding of the surgical consent process for paediatric orthopaedic patients [7,8]. These studies suggest that patient checklists and similar interventions are feasible to use [6][7][8]. To our knowledge, only two studies to date have investigated patient-completed checklists' feasibility and effectiveness.…”
Section: Introductionmentioning
confidence: 99%